A novel switch control scheme for concise S–SSHI array interface with multiple piezoelectric energy harvesters. (March 2023) - Qi, Yuyao; Xia, Yinshui
Abstract: Energy harvesting array formed by multiple piezoelectric transducers (PZTs) can concurrently supply power to the load to improve the reliability. However, the switch control scheme adopted by the existing extensible parallel/series synchronized switch harvesting on inductor interfaces use either dual inductors or redundant peak detectors, both increasing the volume of the circuits. Hence, a novel switch control scheme using RC differential circuit (SCS-RCD) to simplify circuits for multiple piezoelectric harvesters is proposed in this article. It is implemented by reducing the number of switches required for the single piezoelectric block and improving the reuse of components. Extensible S–SSHI (ES-SSHI) circuit based on the SCS-RCD scheme with self-powered performance is proposed. Both theoretical simulation and experimental test demonstrate the effectiveness of the proposed SCS-RCD. The maximum harvested power of prototyped ES-SSHI circuit for single PZT is 3.76 times that of SEH circuit. The results show that the proposed scheme is an alternative option for multiple piezoelectric inputs.